CREDIT ACCOUNTING SALES SYSTEM AT PT. PANGAEA ARGO ADIKARA IN PEKANBARU - Suharti Suharti; Shinta Shinta (Journal of Applied Business and Technology, 2021)
This study aims to determine the effectiveness of the credit sales accounting system used at PT. Pangaea Argo Adikara in Pekanbaru. And to find out the related functions, documents used, accounting record used, procedures used and internal controls in credit sales accounting at PT. Pangaea Argo Adikara. The type used is primary data. The data collection method used in this study was a questionnaire technique. Data analysis techniques used in this study were the sign test method and the descriptive method. The results show that the functions are related, the documents used, the accounting records used, the procedures used, and internal controls have been effective.